Introducing onsite antenatal syphilis screening in Burkina Faso: implementation and evaluation of a feasibility intervention tailored to a local context - Fadima Yaya Bocoum; Grissoum Tarnagda; Fabrice Bationo; Justin R. Savadogo; Sarata Nacro; Séni Kouanda; Christina Zarowsky (BMC, 2017)
Abstract Background Although the advantages of introducing point of care testing for syphilis in antenatal care (ANC) are well documented, there is little evidence on how to address structural issues within health systems. A better understanding of how these interventions work in a range of settings and contexts is needed in order to overcome bottlenecks at health system level. To better understand the relationships between implementation and context we developed and implemented an intervention focused on integrating a rapid screening test for syphilis in ANC services in rural primary health care facilities in Burkina Faso. This manuscript describes the intervention and reports on feasibility and acceptability of the intervention, the facilitators and barriers to the implementation of this intervention and the likelihood that point of care test for syphilis will become routinely incorporated in practice. Methods In Kaya Health and Demographic Surveillance System (Kaya HDSS), all 7 primary healthcare facilities were selected for intervention in 2013. A participatory approach was used to design and implement an antenatal syphilis screening intervention. The Normalization Process Model (NPM) proposed by May et al. was adapted in order to identify barriers and facilitators and to explore the likelihood to become routinely incorporated in practice. Registers, Observations (n = 14 ANC 1) of interactions between patients and health workers during ANC and interviews with health workers (n = 14) were our data sources. Results An intervention that included onsite training, provision of supplies and medicines, quality control and supervision was implemented in 7 health facilities in 2013. Rapid syphilis test and treatment were delivered during ANC within the examination room with no specific additional mechanism regarding staff organization. The perceived barriers were lack of training of all staff, workload, stock-outs of consumables and lack of motivation of staff. Key facilitators included political environment, ease of use of test and acceptability to pregnant women. Conclusions Onsite testing for antenatal syphilis is a feasible and acceptable intervention in ANC at primary health facility in Burkina Faso. The point-of care test for syphilis is more likely to be acceptable by health workers as routine service and incorporated as a normal practice. Trial registration The study was retrospectively registered on ClinicalTrials.gov under the Trial Registration Number NCT03156751 .